Efficacy and safety of pharmacological venous thromboembolism prophylaxis following liver resection: a systematic review and meta-analysis. Issue 4 (April 2017) - Baltatzis, Minas; Low, Ryan; Stathakis, Panagiotis; Sheen, Aali J.; Siriwardena, Ajith K.; Jamdar, Saurabh
Abstract: Background: Current guidelines recommend pharmacological prophylaxis for patients undergoing abdominal surgery for malignancy. Liver resection exposes patients to risk factors for venous thromboembolism, but there is a risk of bleeding. The aim of this study is to evaluate the evidence base supporting the use of pharmacological thromboprophylaxis in liver surgery. Methods: An electronic search was carried out for studies reporting the incidence of VTE following liver resection comparing patients receiving pharmacological prophylaxis with those who did not. The search resulted in 990 unique citations. Following the application of strict eligibility criteria 5 studies comprise the final study population. Results: Included studies report on 3675 patients undergoing liver resection between 1999 and 2013. 2256 patients received chemical thromboprophylaxis, 1412 had mechanical prophylaxis only and 7 received no prophylaxis. Meta-analysis revealed lower VTE rates in patients receiving chemical thromboprophylaxis (2.6%) compared to without prophylaxis (4.6%) (Dichotomous correlation test, odds ratio: 0.631 [95% Cl: 0.416–0.959], Fixed model, p = 0.030). Data regarding bleeding could not be pooled for meta-analysis, but chemical thromboprophylaxis was reported as safe in four studies. Conclusion: This systematic review and meta-analysis of retrospective studies indicates that the use of perioperative chemical thromboprophylaxis reduces VTE incidence following liver surgery without an apparent increased risk of bleeding.